Pengembangan Atraksi Ekowisata Mangrove Berbasis Masyarakat di Kawasan Pesisir Desa Tateli Dua, Kab. Minahasa, Provinsi Sulawesi Utara - Bet El SIlisna Lagarense; Mex U. Pesik (PolimdoSains, 2021)
: Study on the design of ecotourism attraction at the coastal area of Tateli 2 village , Mandolang Sub district, Minahasa Regency. The research aims(1) to help the community for further development of mangrove ecotourism zone of Tateli 2 Village supported by Underwater Ecotourism Students, Manado State Polytechnic (2) to enhance the coastal environmental conservation in Tatali 2 Village as well as design the mangrove attraction ; (3)improve the competence of the community and students in utilizing the ecotourism based environment. The method used is demonstration method , i.e demonstrating a process or an activity through some stages: Preparation Stage, Execution stage and Demonstration Stage.The results of research show that: (1)The local community of Tateli 2 Village have local knowledge about their region as a zone where mangrove can grow for the mangrove attraction development in which the EBL campus, Manado State Polytechnic is located; (2)By involving the local community, it is possible to establish the conservation cadre group that will continuously be assisted by the proposing team in order that they will be able to develop mangrove attraction in their own region sustainably ; (3) Partner contribution, meaning that the coastal community have strengthened the sustainable process of the attraction being developed because the local community have better knowledge about their region and have a high sense of belonging.